Formulation and Evaluation of Mouth Dissolving Film of Imipramine HCL - Mishra, Soumya; Bais, Nidhi; Kumar Jain, Sachin (Journal of Biomedical and Pharmaceutical Research, 2023)
The main objective of the present study outlines a systematic approach for Design and Evaluation of Fast Dissolving Oral Films of Imipramine HCl to enhance the therapeutic efficacy and provide rapid onset of action in patients suffering from depression Because of patient may have trouble in swallowing a tablet or capsules. Mouth dissolving film is the most advanced oral solid dosage form due to its flexibility and comfort in use. Mouth dissolving films are oral solid dosage form that disintegrate and dissolve within a minute when placed in mouth without taking water or chewing. This dosage form allows the medication to bypass the first pass metabolism so bioavailability of medication may be improved. Fast dissolving Oral film of Imipramine Hydrochloride was formulated by using solvent casting method with different concentrations of HPMC-E3. Film forming property of various grades of HPMC was investigated based on preliminary characteristics of various batches of FDOFs.